Current practice of pre-operative assessment at a public sector hospital in Pakistan – a clinical audit - Urooj, Sana; Mughal, Anum; Siddiqui, Sarush Ahmed; Kamal, Rabia; Naeem, Aisha (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the practice of ordering unnecessary laboratory investigations by primary surgical teams. Method: The clinical audit was conducted from December 17, 2022, to January 15, 2023, at the Civil Hospital, Karachi, and comprised primary surgeons working in different surgical units who ordered laboratory investigations for patients as a part of preoperative assessment. Data was collected using a self-administered questionnaire. Data was analysed using SPSS 20. Results: Of the 280 surgeons approached, 249(89%) responded. The units covered were General surgery 96(38.5%), Gynaecology 74(29.7%), Neurosurgery 5(2.0%), Ear, Nose and Throat 19(7.6%), Plastic surgery 15(6.02%), Paediatric surgery 13(5.2%), Vascular surgery 8(3.21%), Oromaxilofacial 9(3.61%), Opthalmology 6(2.4%), and Orthopaedics 4(1.60%).As part of baseline investigations, 244(98%) surgeons ordered complete blood count, 173(69.5%) ordered urea and creatinine, 229(92%) ordered viral markers, 197(78.7%) ordered fasting and random blood glucose, and 178(71.5%) focussed on cardiac fitness. Conclusion: There was a found a need for standard protocols for pre-surgery evaluation so that unnecessary investigations may be avoided. Key Words: Preoperative, Investigation, Guidelines, Assessment, Audit.